National survey on the current practice and attitudes toward the management of chronic subdural hematoma. Issue 3 (3rd February 2022) - Holl, Dana C.; Blaauw, Jurre; Ista, Erwin; Dirven, Clemens M.F.; Kho, Kuan H.; Jellema, Korné; van der Gaag, Niels A.; Miah, Ishita P.; den Hertog, Heleen M.; van der Naalt, Joukje; Jacobs, Bram; Verbaan, Dagmar; et al.
Abstract: Background: Chronic subdural hematoma (CSDH) is a frequent pathological entity in daily clinical practice. However, evidence‐based CSDH‐guidelines are lacking and level I evidence from randomized clinical trials (RCTs) is limited. In order to establish and subsequently implement a guideline, insight into current clinical practice and attitudes toward CSDH‐treatment is required. The aim is to explore current practice and attitudes toward CSDH‐management in the Netherlands. Methods: A national online survey was distributed among Dutch neurologists and neurosurgeons, examining variation in current CSDH‐management through questions on treatment options, (peri)operative management, willingness to adopt new treatments and by presenting four CSDH‐cases. Results: One hundred nineteen full responses were received (8% of neurologists, N  = 66 and 35% of neurosurgeons, N  = 53). A majority of the respondents had a positive experience with burr‐hole craniostomy (93%) and with a conservative policy (56%). Around a third had a positive experience with the use of dexamethasone as primary (30%) and additional (33.6%) treatment. These numbers were also reflected in the treatment preferences in the presented cases. (Peri)operative management corresponded among responding neurosurgeons. Most respondents would be willing to implement dexamethasone (98%) if equally effective as surgery and tranexamic acid (93%) if effective in CSDH‐management. Conclusion: Variation was found regarding preferential CSDH‐treatment. However, this is considered not to be insurmountable when implementing evidence‐based treatments. This baseline inventory on current clinical practice and current attitudes toward CSDH‐treatment is a stepping‐stone in the eventual development and implementation of a national guideline.